Factors affecting thwe breeding success of the South Polar skua Catharacta mackormicki at Edmonson Point, Victoria Land, Antarctica - PEZZO, F.; OLMASTRONI, S.; CORSOLINI, S.; FOCARDI, S. (Polar Biology, 2001)
A south polar skua (Catharacta maccormicki) population was studied at Edmonson Point (74°20′S-165°08′E), Victoria Land, Antarctica, in 1998/1999. The local population consisted of 101 pairs, 89 of which were located within a large, loose colony associated with a rookery of about 2,000 pairs of Adélie penguin (Pygoscelis adeliae). Skua nests were clumped around penguin subcolonies. Mean skua Nearest Neighbour Distance (NND) was 21 ± 15 m (n = 89). NND was positively correlated with the distance from the nearest penguin subcolony. Mean laying date was 24 ± 6 December (n = 89). Mean clutch size was 1.9 ± 0.2 eggs (n = 89). Hatching success was 77% (n = 174 eggs laid), and 20.2% of the breeding pairs successfully raised chicks to fledging. Mean number of fledged young was 0.2 ± 0.4 per breeding pair (n = 89), and 1 per successful pair (n = 18). Main causes of breeding failure were intraspecific predation and sibling aggression. Breeding success was negatively related to distance from the nearest penguin nest and to laying date. Because of the extensive and persistent sea-ice cover, penguins represented an important source of food for the skua population.